A Comparative Study of Transdermal Buprenorphine and Oral Morphine in the Treatment of Chronic Pain of Malignant Origin - Choudhury, Kakali (Indian J Palliat Care, 2018)
BACKGROUND AND OBJECTIVE: The study was designed to compare the efficacy and adverse effects of buprenorphine transdermal (TD) against oral morphine in pain management of cancer patient. METHODS: A randomized open-labeled prospective study was done in palliative cancer pain clinic in a tertiary care medical college between August 2017 and January 2018, to compare the efficacy (pain assessed by VAS) and adverse events (CTCAEv4) between arm A, buprenorphine TD, (20 μg/h, extended 7 days formulation) and arm B, oral morphine (10mg immediate releasing formulation). Patients with solid tumour malignancies with VAS score >40 (moderate to severe pain) were included in study. RESULTS: 63 patients were analyzed. Commonest primary cancers were breast in females and head and neck in male individuals in both arms. Initial VAS score of arm A and arm B were 81.25 and 82.26 respectively. By 1st week, 11 arm A patients were relieved from pain. Another 17 patients of arm A became pain free by 2nd week, total dose of 40 μg/h. Only 4 patients needed 60 μg/h for pain relief. In arm B, 2 patients were relieved by 1 week with total 30mg/day morphine, 11patients were relieved with 60 mg/day by 2nd week and 12 patients with 90 mg/day. 6 patients were relieved with 120 mg/day dose at the end of 4(th) week. Nausea and constipation were stastically higher in Arm B compared to that of Arm-A. CONCLUSIONS: TD Buprenorphine had similar efficacy with oral morphine, with better toxicity profile and better compliance.